Exo‐ and surface proteomes of the probiotic bacterium Lactobacillus acidophilus NCFM. Issue 11 (8th June 2017) - Celebioglu, Hasan Ufuk; Svensson, Birte
Abstract : Lactobacillus acidophilus NCFM is a well‐known probiotic bacterium extensively studied for its beneficial health effects. Exoproteome (proteins exported into culture medium) and surface proteome (proteins attached to S‐layer) of this probiotic were identified by using 2DE followed by MALDI TOF MS to find proteins potentially involved in bacteria–host interactions. The exo‐ and surface proteomes included 43 and 39 different proteins from 72 and 49 successfully identified spots, respectively. Twenty‐two proteins were shared between the two proteomes; both contained the major surface layer protein that participates in host interaction as well as several well‐known and putative moonlighting proteins. The exoproteome contained nine classically‐secreted (containing a signal sequence) and ten nonclassically‐secreted proteins, while the surface proteome contained four classically‐secreted and eight nonclassically secreted proteins. Identification of exo‐ and surface proteomes contributes describing potential protein‐mediated probiotic–host interactions.